"Europe is already all around, but no one notices": The Europeanization of public spheres in regional newspaper reporting - Anke Offerhaus; Anne Mollen; Andreas Hepp (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2014)
So far the news coverage on the EU and on Europe within regional newspapers has not been subject to the research on European public spheres, although regional papers target a broader readership than quality papers and in contrast to TV news also cover regional and local issues along with international and national topics. Therefore, our study aimed at analysing, in how far the European integration process is reflected in the regional press across countries and from a longitudinal perspective. In order to do so, we conducted a standardized content analysis of the political reporting in Danish, German, French, British, Austrian and Polish regional papers from 1982 until 2008. The results show patterns that are already known from the analysis of quality and tabloid reporting: Until the year 2003 the visibility of EU institutions indicate a significant trend of vertical Europeanization, while the references towards other EU member countries point to a slight tendency of horizontal Europeanization, however already starting from a fairly high level. Hardly visible were indicators of processes of identification with Europe: there were only a small number of We-references and the category "the Europeans" even became less important. At the same time, the already strong role of nation states partly gained even more importance as a reference point in the newspaper coverage, especially in between 2003 and 2008. – – Die EU- und Europa-Berichterstattung in Regionalzeitungen ist ein bislang kaum berücksichtigter Gegenstand der europäischen Öffentlichkeitsforschung, obwohl sie eine breitere Leserschaft als Qualitätszeitungen und im Unterschied zur Fernsehberichterstattung neben internationalen und nationalen Themen auch regionale und lokale Themen berücksichtigen. Ziel unserer Studie war es daher länder- und zeitvergleichend zu untersuchen, in welchem Maße sich der europäische Integrationsprozess in der regionalen Presse widerspiegelt. Hierzu wurde eine standardisierte Inhaltsanalyse politischer Berichterstattung dänischer, deutscher, französischer, britischer, österreichischer und polnischer Regionalzeitungen zwischen 1982 bis 2008 durchgeführt. Die Ergebnisse zeigen Muster wie sie auch aus Analysen der Qualitäts- und Boulevardberichterstattung bekannt sind: Bis zum Jahr 2003 konnte anhand der Sichtbarkeit der EU-Institutionen ein deutlicher Trend vertikaler, und anhand der Referenzen auf andere Mitgliedsstaaten, von einem sichtbaren Einstiegslevel ausgehend, ein leichter Trend horizontaler Europäisierung beobachtet werden. Kaum erkennbar waren hingegen Anzeichen europäischer Identifikationsprozesse: es gab nur wenige europäische Wir-Bezüge; die Kategorie "die Europäer" verlor sogar an Bedeutung. Daneben wurde insbesondere zwischen 2003 und 2008 die immer noch starke, z.T. auch stärker werdende Rolle der Nationalstaaten als Bezugspunkte der Berichterstattung deutlich.
Keywords: 300